1775-76 Mass. Acts 31-32, 35 - (:unkn) unknown (My University, 1776)
Act of Mar. 14, 1776, ch. VII: Recommended the disarming of persons who are "notoriously disaffected to the cause of America, or who refuse to associate to defend by arms the United American Colonies."
Keywords: POSSESSION - DANGEROUS PERSONS